An analysis of the visual results when using toric lenses in cataract surgery - Grumann Junior,Astor (2015)
Purpose: To evaluate the postoperative results when using the toric IOL during phacoemulsification. Methods: Retrospective cohort based study on the 95 eyes of 67 patients, selected by a census. Analyzed patients with cataracts who had undergone phacoemulsification placement with AcrySof® toric IOL from january 2010 to december 2012. For analysis purposes, it was considered successful when the residual astigmatism was d”0.75 diopters. The Wilcoxon test for related samples was used to compare non-parametric samples, while the Student T test was used for samples with normal distribution. A p d”0.05 significance level was granted. Results: The average age of the population was 73.00 (±10.87), there was a higher incidence of females (56.8%) and no difference in the side of the affected eye. The average preoperative spherical component was 0.86 (±2.89), since the average cylindrical component was -1.53 (±1.09), with a predominance of the shaft against the rule (51.6%). The logarithmic visual acuity (logMAR) preoperative average was 0.32 (±0.25). The average postoperative spherical component was -0.02 (±0.53). Surgical success was obtained in 71 eyes (74.7%) having a significant decrease (p <0.001) in the cylindrical component and postoperative logarithmic visual acuity, with the respective values of - 0.61 (±0.55) and 0.08 (±0.14), with the remaining axis against the rule (33.7%). Conclusions: The toric lenses were safe and reproducible with regards to postoperative results and therefore an important option for obtaining excellent final refractometric results.